Communication Barriers Between Father and Male Adolescent Regarding Sexual Education - Michelle Fuzhigi; Intan Primadini (Populasi, 2026)
Sexual education is the education to understand about cognitive, emotional, social, physical, and the sexual development of individuals to gain and accept different roles that correlates with sexual health, sexual activity, and sexual identity. The problem of this research is the increasing number of sex before marriage case in Indonesia. It is discovered that the number of male adolescent that have done sex before marriage is higher than that of female adolescent. Sexual education is known to lower the number of sex before marriage but a new problem emerges when parents, specifically fathers refuse to give sexual education to their male adolescent. This research has the purpose to know the reason and the communication barrier that makes fathers not want to give their male adolescent sexual education. This research is using a descriptive qualitative approach using the case study method from Stake (1995). Research is also using an in-depth-interview to gain data. The result of this research is that fathers who already gave their male adolescent sexual education is known to almost always communicate interpersonally with their male adolescent. Meanwhile, the fathers that hasn’t given sexual education is known to rarely communicate interpersonally with their male adolescent. The conclusion of this research is that interpersonal communication is very important to deepen the bonds between father and male adolescent and depending on their relationship, fathers will have an easier time explaining sexual education to their male adolescent.